2020
DOI: 10.1038/s41386-020-0730-z
|View full text |Cite
|
Sign up to set email alerts
|

Opioid antagonists are associated with a reduction in the symptoms of schizophrenia: a meta-analysis of controlled trials

Abstract: Current treatments for the symptoms of schizophrenia are only effective for positive symptoms in some individuals, and have considerable side effects that impact compliance. Thus, there is a need to investigate the efficacy of other compounds in treating both positive and negative symptoms. We conducted a meta-analysis of English language placebo-controlled clinical trials of naloxone, naltrexone, nalmefene, and buprenorphine in patients with schizophrenia to determine whether opioid antagonists have therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Based on this evidence from preclinical studies and in light of the excess striatal dopamine function in schizophrenia underlying psychosis and its response to D2 blockade [ 37 ], and the evidence for supersensitized D2 receptors from imaging studies of comorbid schizophrenia and addiction [ 38 ], we propose that KORs may contribute to the positive symptoms of schizophrenia by interacting at least partly with the dopaminergic system to produce increased dopamine release and supersensitized D2 receptors and may be uniquely positioned to play a therapeutic role. This view is supported by studies of KOR agonists and antagonists that we summarize briefly below, and a meta-analysis that we have recently published [ 39 ]. A dopaminergic mediated effect of KOR agonists does not exclude potentially other non dopaminergic mechanisms that may lead to psychosis.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Based on this evidence from preclinical studies and in light of the excess striatal dopamine function in schizophrenia underlying psychosis and its response to D2 blockade [ 37 ], and the evidence for supersensitized D2 receptors from imaging studies of comorbid schizophrenia and addiction [ 38 ], we propose that KORs may contribute to the positive symptoms of schizophrenia by interacting at least partly with the dopaminergic system to produce increased dopamine release and supersensitized D2 receptors and may be uniquely positioned to play a therapeutic role. This view is supported by studies of KOR agonists and antagonists that we summarize briefly below, and a meta-analysis that we have recently published [ 39 ]. A dopaminergic mediated effect of KOR agonists does not exclude potentially other non dopaminergic mechanisms that may lead to psychosis.…”
mentioning
confidence: 72%
“…Naloxone, naltrexone, and nalmefene, antagonists at the kappa, mu, and delta receptor, and buprenorphine, a dual KOR antagonist and mu partial agonist, have been tested in the treatment of SCZ with various results. We have recently reviewed these studies [ 2 ] and also performed a meta-analysis of all trials which showed a therapeutic signal for KOR antagonism [ 39 ]. Intravenous (IV) naloxone at dosages higher than 4 mg [ 44 , 57 - 63 ] produced significant improvement on the Brief Psychiatric Rating Scale (BPRS), while subcutaneous administration did not [ 64 - 68 ], possibly due to lower bioavailability [ 69 ].…”
mentioning
confidence: 99%
“…To date, there have been more clinical trials of nonselective opioid antagonists for schizophrenia than any other mood disorder, with over 50 clinical trials as well as a number of case reports spanning 4 nonselective opioid antagonists: buprenorphine, nalmefene, naloxone, and naltrexone (Clark et al 2020). The premise for these studies was based on an initial study performed by Gunne and colleagues in 1977 who reported an acute antipsychotic effect of naloxone injection in 4 out of 6 patients with schizophrenia (Gunne et al 1977).…”
Section: Treatment With Nonselective Opioid Antagonists Is Significanmentioning
confidence: 99%
“…Overall, approximately half of these trials did not find any significant effect which makes it difficult to derive any definitive results from any individual trial (Clark and Abi-Dargham 2019). To address this, a recent meta-analysis was conducted on the double-blind placebocontrolled trials of opioid antagonists in patients with schizophrenia (Clark et al 2020). Pooling the trials together resulted in a dataset of 434 patients from 30 trials.…”
Section: Treatment With Nonselective Opioid Antagonists Is Significanmentioning
confidence: 99%
“…First, samidorphan has no drug-drug interaction with olanzapine 14 . Second, opioid antagonists are safe for schizophrenia and may modestly reduce psychotic symptoms 15 . Third, olanzapine/samidorphan is superior to placebo and as effective as olanzapine for the treatment of schizophrenia 16 .…”
Section: Introductionmentioning
confidence: 99%